Assessment of Diagnostic accuracy of Platelet Distribution Width as predictor of Preelampsia - Hifza Saeed, Saima Iqbal, Saema Tehseen, Moizza Aziz (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Assessment of diagnostic accuracy of platelet distribution width in prediction of preeclampsia in females presenting with singleton pregnancy Study Design: A Descriptive case series study. Setting: Department of Obstetrics & Gynecology, Unit II, DHQ Teaching Hospital Gujranwala. Duration of Study: Seven months from 1st March 2019 till 30st September 2019. Methods: Total 170 pregnant females with age ranging between 18-40 years and gestational age from 16-20 weeks having less than 5 children were admitted from OPD of Department of Obstetrics & Gynecology, DHQ hospital, Gujranwala. Females with multiple pregnancy (on ultrasound), those diagnosed with chronic hypertension (BP≥140/90mmHg or taking anti-hypertensive) and those with Liver disease (ALT>40IU, AST>40IU), renal impairment (creatinine > 1.2mg/dl), chronic or gestational diabetes (BSR > 200mg/dl) were excluded. After taking informed consent, patient’s biodata including name, age, BMI, gestational age and parity was noted. At baseline, blood sample was collected in 5cc disposable syringe. Results: All patients were followed-up in OPD till term whereby they were evaluated for blood pressure and presence of proteinuria and preeclampsia was confirmed as positive or negative in accordance with operational definition. Quantitative variables like BMI, age of the patient and gestational age were presented in the form of mean and standard deviation whereas qualitative variables including preeclampsia (on PDW and actual event) were presented in the form of percentage and frequency. Presenting parity as frequency we generated 2x2 table for calculation of NPV, PPV specificity, sensitivity and diagnostic accuracy of PDW taking actual clinical occurrence of preeclampsia as gold standard. Data was stratified for age, parity, BMI of the patient and gestational age calculated in weeks. Conclusion: On the basis of this study we concluded that the PDW is a useful tool for prediction of preeclampsia in females presenting with singleton pregnancy but less had low sensitivity. Keywords: Preeclampsia, Platelet Distribution Width, blood pressure, proteinuria